The KTB superdeep borehole: petrography and structure of a 9-km-deep crustal section - Hirschmann, Günther; Duyster, J.; Harms, U.; Kontny, Agnes; Lapp, M.; Wall, Helga de; Zulauf, G. (Geologische Rundschau, 1997)
The KTB boreholes that were drilled from 1989 to 1994 near Windischeschenbach, NE Bavaria, penetrated rocks of the Zone Erbendorf-Vohenstrauss (ZEV). The upper and lower sections of the 9101m-deep profile are mainly composed of gneiss units (former greywacke sediments) and variegated units (alternating gneisses and metabasites, probably of volcano-sedimentary origin). Metabasic units (amphibolites, metagabbros) constitute mainly the middle section. Geochemical data suggest their derivation from oceanic crust. All rocks are probably pre- to early Ordovician in protolith age. They underwent early Devonian MP metamorphism. Relics of preceeding HP metamorphism are preserved in metagabbros. Felsic to mafic dykes (dominantly Upper Carboniferous lamprophyres) crosscut the metamorphic rocks. The ZEV units are steeply inclined down to the final depth. The main structures (foliation, folds, faults) trend NW-SE. Semibrittle to brittle deformation plays an unexpected important role. In contrast to the conditions of the Mesozoic (mainly Cretaceous/Tertiary) faulting the P-T conditions of MP metamorphism, the cooling ages and the late-Variscan graphite-bearing prehnite-actinolite facies mineralization show no significant depth-dependent gradients. This can be explained by Mesozoic supracrustal stacking. A bundle of reverse faults between 6850 and 7300 m belongs to the Franconian lineament and can be correlated with the most prominent seismic reflector (SE1) in the area.
Gesehen am 24.09.2020